After a Decade: What remains of a kindergarten developmental arts education project? - Nevanen, Saila; Juvonen, Antti; Ruismäki, Heikki (Outlines. Critical Practice Studies, 2014)
This article focuses on the long-term impacts and effects of developmental work that began as an arts education project in Helsinki in 2000. Ten years later, five kindergarten leaders were interviewed to gather information about the impacts of the project. The aim was to determine the long-term effects of the project and examine in which ways the impact could still be seen in the daily work in kindergartens. We also explored the reasons and prerequisites for the impacts still showing, and tried to discover which obstacles prevent the ongoing impact of the developmental work. The interviews showed that the sustainability of the impacts was connected to the organizational changes and the longevity of the personnel in the kindergarten. The developmental work could be better taken advantage of when the kindergarten leaders felt the tasks developed in the project were important and offered them new ideas in their pedagogical leadership. A long-lasting developmental project was seen as part of the process of updating education, which confirmed the participants’ consciousness about being a teacher and the nature of the educational practices as well as a reflective manner of working. Participating also increased general developmental skills and interest in other developmental themes.